Testbuilder for the toeic tests - Beck, Jessica (Macmillan, 2012)
The Testbuilder for the TOEIC Tests offers three complete tests for the Listening & Reading TOEIC test, followed by three tests for the Speaking TOEIC test and three tests for the Writing TOEIC test.